Abiotic and biotic drivers of tree trait effects on soil microbial biomass and soil carbon concentration. Issue 2 (23rd January 2023) - Beugnon, Rémy; Bu, Wensheng; Bruelheide, Helge; Davrinche, Andréa; Du, Jianqing; Haider, Sylvia; Kunz, Matthias; von Oheimb, Goddert; Perles‐Garcia, Maria D.; Saadani, Mariem; Scholten, Thomas; Seitz, Steffen; et al.
Abstract: Forests are ecosystems critical to understanding the global carbon budget, due to their carbon sequestration potential in both aboveground and belowground compartments, especially in species‐rich forests. Soil carbon sequestration is strongly linked to soil microbial communities, and this link is mediated by the tree community, likely due to modifications of microenvironmental conditions (i.e., biotic conditions, soil properties, and microclimate). We studied soil carbon concentration and the soil microbial biomass of 180 local neighborhoods along a gradient of tree species richness ranging from 1 to 16 tree species per plot in a Chinese subtropical forest experiment (BEF‐China). Tree productivity and different tree functional traits were measured at the neighborhood level. We tested the effects of tree productivity, functional trait identity, and dissimilarity on soil carbon concentrations, and their mediation by the soil microbial biomass and microenvironmental conditions. Our analyses showed a strong positive correlation between soil microbial biomass and soil carbon concentrations. In addition, soil carbon concentration increased with tree productivity and tree root diameter, while it decreased with litterfall C:N content. Moreover, tree productivity and tree functional traits (e.g., fungal root association and litterfall C:N ratio) modulated microenvironmental conditions with substantial consequences for soil microbial biomass. We also showed that soil history and topography should be considered in future experiments and tree plantations, as soil carbon concentrations were higher at sites where historical (i.e., at the beginning of the experiment) carbon concentrations were high, themselves being strongly affected by the topography. Altogether, these results implied that the quantification of the different soil carbon pools is critical for understanding microbial community–soil carbon stock relationships and their dependence on tree diversity and microenvironmental conditions.